Evaluation of Naked Barley Landraces for Agro-morphological Traits - Karkee, Ajaya; Ghimire, Krishna Hari; Joshi, Bal Krishna (Journal of Nepal Agricultural Research Council, 2020)
Naked barley (Hordeum vulgare var. nudum L.) is a traditional, culturally important, climate-resilient winter cereal crop of Nepal. Evaluation of the naked barely genotypes for yield and disease is fundamental for their efficient utilization in plant breeding schemes and effective conservation programs. Therefore, to identify high yielding and yellow rust resistant landraces of naked barley for hilly and mountainous agro-ecosystem, twenty naked barley landraces collected from different locations of Nepal, were evaluated in randomized complete block design (RCBD) with three replications during winter season of 2016 and 2017 at Khumaltar, Lalitpur, Nepal. Combined analysis of variances revealed that NGRC04902 (3.46 t/ha), NGRC00886 (3.28 t/ha), NGRC02309 (3.21t/ha) and NGRC06026 (3.10 t/ha) were the high yielding landraces and statistically at par with the released variety 'Solu Uwa' (3.15 t/ha). The landraces namely NGRC00837 (ACI Value: 1.86) was found resistant to yellow rust diseases. Landraces NGRC06034 (131.7 days) and NGRC02363 (130.8 days) were found early maturing and NGRC02306 (94.36 cm) was found dwarf landraces among tested genotypes. These landraces having higher yield and better resistance to yellow rust need to be deployed to farmers' field to diversify the varietal options and used in resistant breeding program to improve the productivity of naked barley for Nepalese farmers.